2023
DOI: 10.1186/s12951-023-01855-w
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Lnc NEAT1 from endothelial cells promote bone regeneration by regulating macrophage polarization via DDX3X/NLRP3 axis

Abstract: Background Bone regeneration is a complex procedure that involves an interaction between osteogenesis and inflammation. Macrophages in the microenvironment are instrumental in bone metabolism. Amount evidence have revealed that exosomes transmitting lncRNA is crucial nanocarriers for cellular interactions in various biotic procedures, especially, osteogenesis. However, the underlying mechanisms of the regulatory relationship between the exosomes and macrophages are awaiting clarification. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Previous studies have confirmed that LNCRNAs. 131 and miRNAs. 132 in ECs-EVs may be involved in osteoporosis.…”
Section: The Potential Role Of Evs Derived From Different Sources In ...mentioning
confidence: 99%
“…Previous studies have confirmed that LNCRNAs. 131 and miRNAs. 132 in ECs-EVs may be involved in osteoporosis.…”
Section: The Potential Role Of Evs Derived From Different Sources In ...mentioning
confidence: 99%
“…The use of a hydrogel-exosome system to fill bone defect areas has represented a novel therapeutic approach for its adaptability. On the one hand, appropriate pretreatment of exosome donor cells, such as 3D cultivation, lentiviral engineering, overexpression or knockdown of function-related miRNAs, and hypoxic stimulation, can enhance the exosome's production, targeting capability, and functions related to bone regeneration [ [263] , [264] , [265] , [266] ]. On the other hand, various biomaterials can produce distinct chemical signals, influencing cell communication and cellular microenvironment, thereby regulating exosome secretion [ 267 ].…”
Section: Application Of the Hydrogel-exosome System For Tissue Repair...mentioning
confidence: 99%
“…The rational use of alginate/methacryloyl gelatin composite hydrogels can effectively protect and release exosomes derived from human umbilical vein endothelial cells and regulate macrophages through the DDX 3X / NLRP3 axis to reduce inflammation and promote skull regeneration. [154] Because of the good reproducibility of the bone tissue, whether it is to promote the proliferation and differentiation of targeted cells or to regulate the immune system of the body, it often plays a role in accelerating repair while facing nonself-repairing cartilage tissue damage. Repairing cartilage tissue A) Composite scaffolds based on collagen and chitosan load exosomes to promote bone regeneration.…”
Section: Composite-based Ev Delivery Platformmentioning
confidence: 99%